Molecular dynamics study of solvated aniline and ethylene glycol monomers confined in calcium silicate nanochannels: a case study of tobermorite. Issue 23 (31st May 2017) - Zhou, Yang; Hou, Dongshuai; Jiang, Jinyang; She, Wei; Li, Jiaqi
Abstract : The combination of organic and inorganic materials can result in materials with extraordinary performance. Abstract : The combination of organic and inorganic materials can result in materials with extraordinary performance. In this work, molecular dynamics was employed to investigate the structure, dynamics, interfacial behavior, and polymerization tendency of two types of monomers, aniline (AN) and ethylene glycol (EG), confined in the nanopores of calcium silicate hydrate (C-S-H) gel. The interaction mechanism between the polymer and C-S-H gel has been interpreted: the silicate chains can provide nonbridging oxygen sites to accept H-bonds from the hydroxyl in EG and –NH2 functional groups in AN monomers. Due to stronger H-bond interactions, EG monomers are more likely to penetrate deeper into the C-S-H surface and exhibit a more pronounced orientation preference and longer resident time in the interfacial region compared with AN monomers. However, neighboring AN monomers exhibit strong spatial correlation and prefer to aggregate as large clusters, while EG monomers diffuse separately in bulk solution. Dynamically, the diffusion coefficients of monomers in the vicinity of the C-S-H surface were greatly reduced compared with those in the bulk solution due to restriction by H-bonds and attraction to surface calcium ions. Furthermore, with increasing monomer concentration, both monomers achieved greater surface adsorption density and penetration depth, and longer interfacial resident times. Higher concentrations also contributed to increased cluster size for AN monomers. The interaction mechanism in this organic–inorganic system provides useful guidelines for polymer selection, design, and fabrication of C-S-H/polymer nanocomposites.